The role of pulmonary metastasectomy in patients suffering pancreatic ductal adenocarcinoma with lung metastases: a systematic review and meta-analysis - Zhao, Pengcheng; Jiang, Qiaoqi; Xue, Kang; Liu, Xiaofeng; Tian, Bole (Frontiers in Surgery, 2025)
BackgroundBecause of the high rate of recurrence, the prognosis of patients with pancreatic ductal adenocarcinoma (PDAC) is still very poor despite underwent pancreatectomy and adjuvant chemotherapy. A few reports have suggested the feasibility and efficacy of surgical resection for pulmonary metastases of PDAC. However, the role of metastasectomy of recurrent PDAC remains controversial. The aim of this study is to evaluate the benefits of pulmonary metastasectomy in PDAC patients with lung metastases.MethodsWe searched the PubMed, Embase, and Cochrane Library databases and extracted the hazard ratio (HR) with 95% confidence interval (CI) from eligible studies. Pooled HR with 95% CI were used to reveal the association between pulmonary metastasectomy and survival.ResultsThe meta-analysis encompassed data from nine studies, comprising 467 patients suffered PDAC with lung metastasis. The results (the pooled HR: 0.637, 95% CI: 0.531–0.764, I2 = 61.5%, p value = 0.008) indicated that patients with lung metastasis who underwent pulmonary metastasectomy seemed to have better survival when compared with patients who underwent only chemotherapy. The robustness of these pooled results was verified by our subgroup analysis and sensitivity analysis. Moreover, the varying sample sizes among studies contribute to the heterogeneity in the pooled hazard ratio (HR) for survival, as indicated by the meta-regression analysis (p value = 0.045).ConclusionPulmonary metastasectomy could prolong the survival in patients with lung metastases from PDAC. However, the present study is based on a relatively small number of patients and may include a selection bias. More multi-institutional prospective study is needed to evaluated the clinical value of pulmonary metastasectomy.